EXAMINING THE EFFECT OF SALICYLIC ACID AND JASMONIC ACID ON THE EXPRESSION OF PR1, NPR1, PAL AND WRKY GENES OF MELON AGAINST ZUCCHINI YELLOW MOSAIC VIRUS - Hossein Ali Mirhosseini, Saeed Nasrollahnejad, Valiollah Babaeizad (International Journal of Modern Agriculture, 2021)
Zucchini yellow mosaic virus (ZYMV) is one of the critical viruses of the cucurbits with worldwide spread leading to significant damage to them. The induction of pathogen-related genes with a role in disease resistance can affect the severe reduction of the disease. The evidence shows that plant hormones are effective in expressing these genes among plants. Furthermore, it stimulates the plant immune system through the activation of transcription of genes involved in the plant defense mechanism and leads to long-term resistance against a wide range of pathogens like viruses. The study examined the expression of PR1, NPR1, PAL, and WRKY genes in melon plants treated with salicylic acid at a concentration of 3 mM and jasmonic acid at a concentration of 0.5 mM and the control plant after inoculation using ZYMV in four different time intervals using Quantitative Real-time PCR (QRT-PCR) technique. The results revealed that treatment with these two hormones, particularly salicylic acid, led to great changes in the expression of these genes following inoculation of the virus into the plant. For the first time in Iran, the study examined the induction of PR1, NPR1, PAL, and WRKY genes in melon resistance to ZYMV.